PENGEMBANGAN MEDIA PEMBELAJARAN KOMIK DIGITAL BERBASIS SEJARAH LOKAL PERANG SOSOH PADA MATERI AGRESI MILITER II KELAS XII SMAN 2 MANDAU - Ananta, Laurentcia; Bunari, Bunari; Yuliantoro, Yuliantoro (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to develop a digital comic media based on the local history of the War of Sosoh that can be used in learning the history of military aggression II material in class XII of SMAN Mandau. The research method used is the Research and Development (RnD) ADDIE model which includes analysis, design, development, implementation, and evaluation. The results of the study show the following: The product was tested for feasibility from the material validation test and received a score of 92.3%. The media validation test received a score of 85.7% with each receiving a very feasible category. After the validation process, the media was tested on students in two stages to see the students' responses. The small group trial received a score of 90.4% and the large group trial received a score of 91.2% with each receiving a response category of "Very Good". This shows that the digital comic media based on the local history of the War of Sosoh is very suitable for use as an alternative media in the history learning process in schools.